Education of civil protection officers in Montenegro - the necessity of systemic reform - Ćupić, Danilo; Korać, Safet (Crisis Management Days, 2024)
The basis of modern security organizations and the prerequisite for their full functionality is their personnel element. Without a educated, trained and qualified officer, the security services cannot aspire to complete and efficient fulfillment of their basic mission - protection of personal and material security of citizens. In Montenegro, there is no specialized higher education institution for personnel in the security services (police, financial police, prison police, communal police, national security, military police, civil protection, private security, etc.). Officers acquire higher education on their own initiative and independently at faculties in the state and region, without a system of scholarships from the service, most often at universities and faculties that have no points of contact with the narrower field of their profession. In this way, the rule was introduced that the diploma is important, and not acquired and adopted knowledge and competences, and there is no fully developed merit system for advancement, so after graduation enter to the service is mostly external, and for the largest number of jobs, with a general condition - completion of a faculty of social, natural, technical-technological or humanistic sciences. The personnel picture of the protection and rescue system do not deviate from this standard. In this work, the authors analyze the system of organization and functioning of the civil protection and rescue service at the national and local level in Montenegro, provide an insight into the existing education and training system for the needs of the security services, and provide recommendations in which direction this system should be reformed and adapted to regional and european experiences, by establishing a higher education institution for the needs of training personnel for the security services, in which a special module will be dedicated to the training of personnel for the civil protection system. The study model according to the 3 (basic) + 2 (master) system seems adequate, with the first two years of common subjects, while in the third year there would be a choice of specialization - police, prison police, military police, customs and tax police, communal police, national security, civil protection and private security.